Functional consequences of a rare human serotonergic 5-HT1A receptor variant - Tauber, Merav; Ben-Chaim, Yair (Frontiers in Pharmacology, 2023)
Serotonin (5-HT) plays a central role in various brain functions via the activation of a family of receptors, most of them G protein coupled receptors (GPCRs). 5-HT1A receptor, the most abundant 5-HT receptors, was implicated in many brain dysfunctions and is a major target for drug discovery. Several genetic polymorphisms within the 5-HT1A receptor gene were identified and linked to different conditions, including anxiety and depression. Here, we used Xenopus oocytes to examine the effects of one of the functional polymorphism, Arg220Leu, on the function of the receptor. We found that the mutated receptor shows normal activation of G protein and normal 5-HT binding.On the other hand, the mutated receptor shows impaired desensitization, probably due to impairment in activation of β arrestin-dependent pathway. Furthermore, while the 5-HT1A receptor was shown to exhibit voltage dependent activation by serotonin and by buspirone, the mutated receptor was voltage-independent. Our results suggest a pronounced effect of the mutation on the function of the 5-HT1A receptor and add to our understanding of the molecular mechanism of its voltage dependence. Moreover, the findings of this study may suggest a functional explanation for the possible link between this variant and brain pathologies.